Intravital two-photon microscopy of lymphatic vessel development and function using a transgenic Prox1 promoter-directed mOrange2 reporter mouse. (21st November 2011) - Hägerling, René; Pollmann, Cathrin; Kremer, Ludmila; Andresen, Volker; Kiefer, Friedemann
Abstract : Lymphatic vessels, the second vascular system of higher vertebrates, are indispensable for fluid tissue homoeostasis, dietary fat resorption and immune surveillance. Not only are lymphatic vessels formed during fetal development, when the lymphatic endothelium differentiates and separates from blood endothelial cells, but also lymphangiogenesis occurs during adult life under conditions of inflammation, wound healing and tumour formation. Under all of these conditions, haemopoietic cells can exert instructive influences on lymph vessel growth and are essential for the vital separation of blood and lymphatic vessels. LECs (lymphatic endothelial cells) are characterized by expression of a number of unique genes that distinguish them from blood endothelium and can be utilized to drive reporter genes in a lymph endothelial-specific fashion. In the present paper, we describe the Prox1 (prospero homeobox protein 1) promoter-driven expression of the fluorescent protein mOrange2, which allows the specific intravital visualization of lymph vessel growth and behaviour during mouse fetal development and in adult mice.